Thermoplastic resin composition, method for preparing same, and molded article comprising same
By using regenerated polycarbonate resin, graft copolymer and flame retardant in the thermoplastic resin composition, the problem of degradation of physical properties of the polycarbonate resin when mixed is solved, and the impact resistance and flame retardancy of the composition are improved, and it is suitable for the production of electrical and electronic components.
Patent Information
- Application Number
- CN202411411682.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-26
- Filing Date
- 2024-10-10
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, polycarbonate resin is prone to transesterification reaction when mixed with other materials, resulting in a decrease in physical properties, and it is difficult to take into account both mechanical strength and flame retardancy in electrical products.
A thermoplastic resin composition has been developed, including post-consumer regenerated polycarbonate resin, vinyl cyano compound-conjugated diene compound-aromatic vinyl compound graft copolymer, phosphorus flame retardant, wollastonite and talc. By adjusting the combination ratio and additive type, the impact resistance, molding processability, heat resistance and flame retardant of the composition are improved.
It is achieved to significantly improve the mechanical properties and flame retardant properties of the thermoplastic resin composition while maintaining environmentally friendly characteristics, making it suitable for the manufacturing of electrical and electronic components.
Smart Images

Figure CN119899506A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition, a preparation method thereof and a molded product containing the same, and more particularly to a thermoplastic resin composition which is environmentally friendly due to the inclusion of recycled resin and has excellent impact resistance, molding processability, heat resistance and flame retardancy, a preparation method thereof and a molded product containing the same. Background Art
[0002] Polycarbonate (PC) resin has excellent mechanical, physical and optical properties, and is therefore used in a variety of fields, including automotive interior and exterior materials, and housings for electrical and electronic products. However, PC resin has the disadvantages of low-temperature impact resistance and chemical resistance due to its amorphous properties, so it is mixed with crystalline materials to compensate for this.
[0003] As one of the main crystalline materials mixed with the PC resin, polyester resins represented by polybutylene terephthalate resins or polyethylene terephthalate resins can be cited as examples. However, when PC resins are mixed with polyester resins, transesterification reactions occur, resulting in reduced physical properties. Therefore, additives having transesterification reaction inhibitory effects are required to control this.
[0004] In addition, electrical products have the risk of fire, and therefore need to have flame retardancy above a specified level. Generally, when a flame retardant is added to improve the flame retardancy of PC resin, there is a problem that the mechanical strength is weakened.
[0005] On the other hand, with the global trend of environmental protection, the attention to ESG (Environment, Social and Governance) is increasing, where ESG means responsibility and sustainability for environmental and social impacts. As part of this, in the field of manufacturing using plastics, it is a trend to use recycled resins, which are materials collected and recycled from plastic waste that is becoming a serious environmental problem.
[0006] Virgin resins are widely used in various fields due to excellent processability and low prices, and therefore, there is a considerable amount of such plastic waste.
[0007] Therefore, it is necessary to develop a material that contains an excess of recycled resin to contribute to global environmental protection and has excellent mechanical properties, molding processability, heat resistance, and flame retardancy.
[0008] Prior Art Literature
[0009] Patent document: Korean Patent No. 10-0767428 Summary of the invention
[0010] Technical issues
[0011] In order to solve the above-mentioned problems in the prior art, an object of the present invention is to provide a thermoplastic resin composition which is environmentally friendly due to the inclusion of recycled resin and has excellent impact resistance, moldability, heat resistance and flame retardancy.
[0012] Another object of the present invention is to provide a method for preparing the thermoplastic resin composition.
[0013] Another object of the present invention is to provide a molded article comprising the thermoplastic resin composition.
[0014] The above-mentioned object and other multiple objects of the present invention can all be achieved by the present invention described below.
[0015] Technical Solution
[0016] In order to achieve the above-mentioned object, (I) the present invention provides a thermoplastic resin composition, which comprises: (A) post-consumer recycled polycarbonate resin (post-consumer recycled PC resin); (B) a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (C) a (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (D) a phosphorus flame retardant; (E) a flame retardant aid; (F) wollastonite; (G) talc; and (H) an antioxidant, a lubricant or a combination of the two, wherein the content of the post-consumer recycled polycarbonate resin (A) is 46 to 70% by weight, and the impact strength of the thermoplastic resin composition measured under the condition that the thickness of the sample is 3.2 mm according to the ASTM D256 standard is 5 kgf / cm·cm or more, and the flow index of the thermoplastic resin composition measured under the condition that the temperature is 260°C and the load is 2.16 kg according to the ISO 1133 standard is 6 g / 10 min or more, and the flow index of the thermoplastic resin composition measured under the condition that the temperature is 260°C and the load is 2.16 kg according to the ASTM D256 standard is 5 kgf / cm·cm or more. According to the D648 standard, the heat deformation temperature of the thermoplastic resin composition measured under the conditions of a sample thickness of 6.4 mm and a stress of 1.82 MPa is 85° C. or higher.
[0017] In addition, (II) the present invention provides a thermoplastic resin composition, which comprises: (A) post-consumer recycled polycarbonate resin; (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (D) phosphorus flame retardant; (E) flame retardant additive; (F) wollastonite; (G) talc; and (H) antioxidant, lubricant or a combination of the two, wherein the content of the (A) post-consumer recycled polycarbonate resin is 46 to 70% by weight, the weight ratio of the (F) wollastonite to the (G) talc is 1:0.1 to 1:0.9 (F:G), and the average particle size of the (G) talc is less than 9 μm.
[0018] (III) In the above (I) or (II), preferably, the thermoplastic resin composition may contain: 51 to 70 weight % of (A) post-consumer recycled polycarbonate resin; 2 to 12 weight % of (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 2 to 11 weight % of (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 3 to 20 weight % of (D) phosphorus flame retardant; 0.1 to 5 weight % of (E) flame retardant auxiliary; 10 to 26 weight % of (F) wollastonite; 3 to 20 weight % of (G) talc; and 0.05 to 5 weight % of (H) antioxidant, lubricant or a combination of the two.
[0019] (IV) In the above (I) to (III), preferably, the content of the (A) post-consumer recycled polycarbonate resin may be 51 to 55% by weight.
[0020] (V) In the above (I) to (IV), preferably, according to ISO 1133 standard, the flow index of the (A) post-consumer recycled polycarbonate resin measured at 300° C. and 1.2 kg may be 3 to 17 g / 10 min.
[0021] (VI) Among the above (I) to (V), preferably, the (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer may contain 40 to 80 weight % of conjugated diene rubber, 5 to 35 weight % of aromatic vinyl compound and 5 to 35 weight % of vinyl cyanide compound.
[0022] (VII) In (I) to (VI), preferably, the (C) (meth)acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer may contain 40 to 80 weight % of conjugated diene rubber, 10 to 40 weight % of aromatic vinyl compound and 2 to 25 weight % of (meth)acrylate alkyl ester compound.
[0023] (VIII) In (I) to (VII), preferably, the (D) phosphorus flame retardant may be one or more selected from bisphenol A bis(diphenyl phosphate) (BPADP), triphenyl phosphate and resorcinol bis(diphenylphosphate).
[0024] (IX) In the above (I) to (VIII), preferably, the flame retardant auxiliary agent (E) may include a fluorine-based flame retardant auxiliary agent.
[0025] (X) In the above (I) to (IX), preferably, the average particle size of the talc (G) may be 3 to 5 μm.
[0026] (XI) Among the above (I) to (X), preferably, the antioxidant in (H) may include at least one selected from phenolic antioxidants and phosphorus antioxidants.
[0027] (XII) In (I) to (XI), preferably, the lubricant in (H) may include one or more selected from fatty amide compounds, lignite wax, silicone oil, olefin wax and pentaerythritol stearate.
[0028] In addition, (XIII) the present invention provides a method for preparing a thermoplastic resin composition, which comprises the steps of kneading and extruding a mixture containing (A) post-consumer recycled polycarbonate resin, (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer, (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer, (D) phosphorus flame retardant, (E) flame retardant auxiliary, (F) wollastonite, (G) talc and (H) antioxidant, lubricant or a combination of both, wherein the content of (A) post-consumer recycled polycarbonate resin is 46 to 70% by weight, the weight ratio of (F) wollastonite to (G) talc is 1:0.1 to 1:0.9 (F:G), and the average particle size of the (G) talc is less than 9 μm.
[0029] Furthermore, (XIV) the present invention provides a molded article comprising the thermoplastic resin composition.
[0030] (XV) In the above (XIV), preferably, the molded article may be a cover or bezel of an electric or electronic component.
[0031] Beneficial Effects
[0032] According to the present invention, an environmentally friendly thermoplastic resin composition having excellent impact resistance, molding processability, heat resistance and flame retardancy, a method for producing the same, and a molded article produced therefrom can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 : is a schematic diagram showing a bezel made of the thermoplastic resin composition of the present invention included in a notebook computer. DETAILED DESCRIPTION
[0034] Hereinafter, the thermoplastic resin composition of the present invention, the method for producing the same, and the molded article comprising the same will be described in detail.
[0035] The inventors of the present invention have confirmed that by mixing an impact-reinforcing resin, a flame retardant, a filler, etc. into a predetermined recycled resin and adjusting the combination ratio, it is possible to improve the flame retardancy, impact resistance, molding processability, etc. while improving the degradation of physical properties caused by the recycled resin, and based on this, further research has been conducted to complete the present invention.
[0036] The thermoplastic resin composition of the present invention comprises: (A) post-consumer recycled polycarbonate resin; (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (D) phosphorus flame retardant; (E) flame retardant auxiliary; (F) wollastonite; (G) talc; and (H) antioxidant, lubricant or a combination of the two, wherein the content of the (A) post-consumer recycled polycarbonate resin is 46 to 70% by weight, the weight ratio of the (F) wollastonite to the (G) talc is 1:0.1 to 1:0.9 (F:G), and the average particle size of the (G) talc is less than 9 μm. At this time, the recycled resin is included and the composition is environmentally friendly, and the impact resistance, molding processability, heat resistance and flame retardancy are excellent.
[0037] As a preferred example, the thermoplastic resin composition of the present invention may include: (A) post-consumer recycled polycarbonate resin; (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (D) phosphorus flame retardant; (E) flame retardant auxiliary; (F) wollastonite; (G) talc; and (H) antioxidant, lubricant or a combination of the two, wherein, according to ASTM D256 standard, the impact strength of the thermoplastic resin composition measured under the condition that the sample thickness is 3.2 mm is 5 kgf / cm·cm or more, more preferably 5.2 kgf / cm·cm or more, according to ISO 1133 standard, the flow index of the thermoplastic resin composition measured under the condition that the temperature is 260°C and the load is 2.16 kg is 6 g / 10 min or more, more preferably 7 g / 10 min or more, according to ASTM According to the D648 standard, the heat deformation temperature of the thermoplastic resin composition measured under the conditions of a sample thickness of 6.4 mm and a stress of 1.82 MPa is 85° C. or higher, more preferably 85.2° C. or higher. In this case, since the recycled resin is included, it is environmentally friendly, and has excellent impact resistance, molding processability, heat resistance, and flame retardancy.
[0038] In the present invention, the component ratio of the copolymer or the resin may mean the content of the units constituting the copolymer, or the content of the monomers introduced at the time of polymerization of the copolymer.
[0039] In the present invention, a polymer containing a certain compound refers to a polymer containing the compound and polymerized, and units in the polymerized polymer are derived from the compound.
[0040] In the present invention, the recycled thermoplastic resin is not particularly limited, as long as it follows the definition of the present invention and is a recycled thermoplastic resin generally recognized in the art. As an example, it represents a thermoplastic resin recycled from recycled waste plastics. As a specific example, it is a usable raw material state prepared from recycled waste plastics through screening, washing and crushing. In addition, as needed, a granular form processed by an extrusion process can be used, in which case, no additional processing such as additional purification is required. This recycled thermoplastic resin has been processed more than once, and therefore, it may contain additives such as colorants, lubricants and / or release agents.
[0041] As a specific example, in the present invention, post-consumer recycled polycarbonate may also be referred to as reused polycarbonate or recycled polycarbonate, for example.
[0042] In the present invention, the non-recycled thermoplastic resin is opposite to the recycled thermoplastic resin defined above, and may be a commercially available product directly prepared by polymerizing a plurality of monomers for constituting a thermoplastic resin, and may be referred to as a virgin resin, for example.
[0043] In the present invention, unless otherwise defined, "content" means weight, and unless otherwise defined, "%" means weight %.
[0044] Hereinafter, the thermoplastic resin composition of the present invention will be described in detail according to its various components.
[0045] (A) Post-consumer recycled PC resin
[0046] As an example, in the total 100 wt % of the thermoplastic resin composition, the content of the (A) post-consumer recycled polycarbonate resin can be 46 wt % or more, preferably 46 to 70 wt %, more preferably 46 to 65 wt %, even more preferably 50 to 60 wt %, further preferably 51.2 to 58 wt %, and even more preferably 51.2 to 55 wt %, in which case the impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0047] In the present invention, 100% by weight of the thermoplastic resin composition in total means that the total weight of (A) to (G) added together is 100% by weight.
[0048] As an example, according to ISO 1133 standard, the flow index of the (A) post-consumer recycled polycarbonate resin measured at 300°C and 1.2 kg can be 3 to 17 g / 10 min, preferably 5 to 15 g / 10 min, and more preferably 7 to 13 g / 10 min. Within this range, the molding processability and physical property balance are excellent.
[0049] As an example, the weight average molecular weight of the (A) post-consumer recycled polycarbonate resin may be 3,000 to 50,000 g / mol, preferably 4,000 to 30,000 g / mol, and more preferably 5,000 to 20,000 g / mol. Within this range, impact resistance, molding processability, heat resistance and flame retardancy are more excellent.
[0050] In the present invention, unless otherwise defined, the weight average molecular weight and the number average molecular weight can be measured by GPC (Gel Permeation Chromatography, Waters Breeze). As a specific example, THF (tetrahydrofuran) can be used as an eluent and the weight average molecular weight and the number average molecular weight can be measured by GPC (Gel Permeation Chromatography, Waters Breeze) using relative values based on a standard polystyrene sample. At this time, as a specific measurement example, THF can be used as the solvent, the column temperature is 40°C, the flow rate is 0.3 mL / min, the sample concentration is 20 mg / mL, the injection volume is 5 μL, the column type is 1×PLgel 10μm MiniMix-B (250×4.6 mm) + 1×PLgel10μm MiniMix-B (250×4.6 mm) + 1×PLgel 10μm MiniMix-B Guard (50×4.6 mm), the measuring instrument is Agilent 1200 series system, differential refractometer (Refractive index detector): Agilent G1362 RID, RI temperature is 35°C, data processing uses Agilent ChemStation S / W, and the experimental method (Mn, Mw and PDI) is measured according to OECD TG 118 conditions.
[0051] The type of the (A) post-consumer recycled polycarbonate resin is not particularly limited, but as an example, it may be a resin obtained by polymerizing a bisphenol monomer and a carbonate precursor.
[0052] As an example, the bisphenol monomer can be selected from bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ketone, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A; BPA), 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z; BPZ), 2,2-bis(4-hydroxy-3,5-diphenol A; BPA), 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z; BPZ), 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A; BPA), 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z; BPZ ...cyclohexane (bisphenol Z; BPZ), 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z; BPZ), 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z; BPZ), 1,1-bis(4-hydroxyphenyl)cyclo bromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane and α,ω-bis[3-(ο-hydroxyphenyl)propyl]polydimethylsiloxane.
[0053] As an example, the carbonate precursor can be one or more selected from dimethyl carbonate, diethyl carbonate, dibutyl carbonate, dicyclohexyl carbonate, diphenyl carbonate, xylene carbonate, bis(chlorophenyl) carbonate, di-m-tolyl carbonate, dinaphthyl carbonate, bis(diphenyl) carbonate, phosgene, triphosgene, diphosgene, phosgene bromide and dihaloformates.
[0054] As an example, the (A) post-consumer recycled polycarbonate resin may be one or more selected from linear polycarbonate, branched polycarbonate and polyester carbonate copolymer resin, preferably linear polycarbonate. In this case, the fluidity is improved, and therefore, the molding processability and appearance characteristics are better.
[0055] As a preferred example, the linear polycarbonate may be bisphenol-A type polycarbonate.
[0056] The preparation method of the (A) post-consumer recycled polycarbonate resin is not particularly limited, as long as it is a commonly used preparation method in the art, and as long as it complies with the definition of the present invention, even a commercially available product is acceptable.
[0057] In the present invention, the content of the (A) post-consumer recycled polycarbonate resin is as high as 45% by weight or more, and the recycling ratio is high, so it is environmentally friendly, reduces the consumption of water and energy, and improves heat resistance, impact resistance, flame retardancy, molding processability, etc.
[0058] (B) Vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer
[0059] As an example, in the total 100 wt % of the thermoplastic resin composition, the content of the (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer (hereinafter referred to as "(B) graft copolymer") can be 2 to 12 wt %, preferably 3 to 10 wt %, more preferably 3 to 8 wt %, even more preferably 3 to 7 wt %, and further preferably 3 to 6.7 wt %, in which case the impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0060] As an example, the (B) graft copolymer may contain 40 to 80% by weight of a conjugated diene rubber containing a conjugated diene compound, 5 to 35% by weight of an aromatic vinyl compound and 5 to 35% by weight of a vinyl cyanide compound, preferably 45 to 80% by weight of a conjugated diene rubber, 10 to 30% by weight of an aromatic vinyl compound and 7 to 30% by weight of a vinyl cyanide compound, more preferably 50 to 75% by weight of a conjugated diene rubber, 12 to 30% by weight of an aromatic vinyl compound and 10 to 25% by weight of a vinyl cyanide compound. Within this range, the impact resistance and the balance of physical properties are better.
[0061] As an example, the average particle size of the conjugated diene rubber contained in the graft copolymer (B) may be Preferably More preferably In this range, the impact strength is further improved without deteriorating other physical properties.
[0062] In the present invention, the average particle size of the rubber particles or the (grafted) copolymer is not particularly limited, as long as it is measured by a measurement method commonly used in the art, including electron microscope measurement using SEM, TEM, etc. As an example, it can be measured using a dynamic light scattering method, specifically, it can be measured using a particle measuring instrument (product name: Nicomp 380, manufacturer: PSS) with an intensity value in Gaussian mode. At this time, as a specific measurement example, 0.1 g of latex with a total solid content of 35 to 50% by weight is diluted 1,000 to 5,000 times with distilled water to prepare a sample. The measurement method is to perform automatic dilution and measure using a flow cell. The measurement mode is dynamic light scattering / intensity 300KHz / intensity-weight Gaussian Analysis. The measurement is performed under the following setting values: temperature is 23°C, measurement wavelength is 632.8nm, and channel width is 10μsec.
[0063] As an example, the grafting rate of the graft copolymer (B) may be 20% to 70%, preferably 20% to 55%, and more preferably 20% to 45%. Within this range, compatibility and molding processability are appropriately ensured and the balance with other mechanical properties is excellent.
[0064] As a specific measurement example, the grafting rate of the present invention can be obtained by adding 30 g of acetone to 0.5 g of the grafted copolymer powder, stirring at 210 rpm for 12 hours at room temperature (SKC-6075, Lab companion), and then centrifuging it at 18,000 rpm for 3 hours at 0°C using a centrifuge (Supra R30, Johnny Scientific Co., Ltd.), and only collecting the insoluble matter (gel) insoluble in acetone, measuring the weight after drying at 85°C for 12 hours in a forced circulation manner (OF-12GW, Lab companion), and calculating it using the following mathematical formula 1.
[0065] Mathematical formula 1:
[0066] Grafting rate (%) = [weight of grafted monomer (g) / weight of rubber (g)] * 100
[0067] In the mathematical formula 1, the weight (g) of the grafted monomer is the weight obtained by subtracting the weight (g) of the rubber from the weight (g) of the insoluble matter obtained after the graft copolymer is dissolved in acetone and centrifuged, and the weight (g) of the rubber is the weight (g) of the rubber component theoretically input into the graft copolymer powder.
[0068] As an example, the weight average molecular weight of the graft copolymer (B) may be 20,000 to 800,000 g / mol, preferably 30,000 to 600,000 g / mol. Within this range, the flowability is appropriate, and thus the processability is excellent, and the impact resistance is excellent.
[0069] As an example, the conjugated diene compound contained in the graft copolymer (B) may be at least one selected from 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene and chloroprene, and is preferably 1,3-butadiene.
[0070] As an example, the aromatic vinyl compound contained in the (B) graft copolymer may be one or more selected from styrene, α-methylstyrene, ο-methylstyrene, ρ-methylstyrene, m-methylstyrene, ethylstyrene, isobutylstyrene, tert-butylstyrene, ο-bromostyrene, ρ-bromostyrene, m-bromostyrene, ο-chlorostyrene, ρ-chlorostyrene, m-chlorostyrene, vinyltoluene, vinylxylene, fluorostyrene and vinylnaphthalene, preferably one or more selected from styrene and α-methylstyrene, more preferably styrene. In this case, the fluidity is appropriate, so the processability is excellent, and the mechanical properties such as impact strength are excellent.
[0071] As an example, the vinyl cyanide compound contained in the graft copolymer (B) may be at least one selected from acrylonitrile, methacrylonitrile, ethacrylonitrile, isopropylacrylonitrile, phenylacrylonitrile and α-chloroacrylonitrile, preferably acrylonitrile.
[0072] The (B) graft copolymer is not particularly limited, as long as it is prepared by a preparation method commonly used in the art. For example, it can be prepared by known polymerization methods including emulsion polymerization, suspension polymerization, bulk polymerization, etc., preferably prepared by emulsion polymerization. As long as it complies with the definition of the present invention, even commercially available products are fine.
[0073] (C) (Meth)acrylic acid alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer
[0074] As an example, in the total 100 wt % of the thermoplastic resin composition, the content of the (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer (hereinafter referred to as "(C) graft copolymer") can be 2 to 11 wt %, preferably 2 to 10 wt %, more preferably 3 to 8 wt %, even more preferably 3 to 7 wt %, and further preferably 4 to 6 wt %, in which case the impact resistance, moldability, heat resistance and flame retardancy are all excellent.
[0075] As an example, the (C) graft copolymer may contain 40 to 80% by weight of a conjugated diene rubber, 10 to 40% by weight of an aromatic vinyl compound, and 2 to 25% by weight of an alkyl (meth)acrylate compound, preferably 45 to 80% by weight of a conjugated diene rubber, 15 to 37% by weight of an aromatic vinyl compound, and 3 to 22% by weight of an alkyl (meth)acrylate compound, and more preferably 50 to 75% by weight of a conjugated diene rubber, 20 to 35% by weight of an aromatic vinyl compound, and 3 to 20% by weight of an alkyl (meth)acrylate compound. In this case, the impact resistance is more excellent without reducing other physical properties.
[0076] As an example, the average particle size of the conjugated diene rubber contained in the graft copolymer (C) may be Preferably More preferably In this range, the impact strength is further improved without deteriorating other physical properties.
[0077] As an example, the grafting rate of the graft copolymer (C) may be 20% to 70%, preferably 20% to 55%, and more preferably 20% to 45%. Within this range, compatibility and molding processability are appropriately ensured and the balance with other mechanical properties is excellent.
[0078] As an example, the weight average molecular weight of the graft copolymer (C) may be 30,000 to 500,000 g / mol, preferably 50,000 to 300,000 g / mol. Within this range, the flowability is appropriate, and thus the processability is excellent, and the impact resistance is excellent.
[0079] In the present invention, the (meth)acrylic acid alkyl ester represents a category including both acrylate alkyl ester and methacrylate alkyl ester.
[0080] As an example, the alkyl acrylate contained in the (C) graft copolymer can be an alkyl acrylate having an alkyl group with 1 to 15 carbon atoms, preferably one or more selected from methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylbutyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, heptyl acrylate, n-pentyl acrylate and lauryl acrylate, more preferably an alkyl acrylate having an alkyl group with 1 to 4 carbon atoms, more preferably butyl acrylate, ethylhexyl acrylate or a combination thereof, further preferably butyl acrylate.
[0081] As an example, the alkyl methacrylate contained in the graft copolymer (C) may be an alkyl methacrylate having an alkyl group with 1 to 15 carbon atoms, preferably at least one selected from methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylbutyl methacrylate, 2-ethylhexyl methacrylate and lauryl methacrylate, more preferably an alkyl methacrylate having an alkyl group with 1 to 4 carbon atoms, and even more preferably methyl methacrylate.
[0082] The conjugated diene compound and the aromatic vinyl compound contained in the (C) graft copolymer may be respectively selected from the categories mentioned in the (B) graft copolymer.
[0083] The preparation method of the graft copolymer (C) is not particularly limited as long as it is a commonly used preparation method in the art. For example, it can be prepared by known polymerization methods including emulsion polymerization, suspension polymerization, bulk polymerization, etc., preferably by emulsion polymerization. As long as it complies with the definition of the present invention, even commercially available products are not a problem.
[0084] (D) Phosphorus flame retardants
[0085] As an example, in the total 100 wt % of the thermoplastic resin composition, the content of the (D) phosphorus flame retardant can be 3 to 20 wt %, preferably 6 to 20 wt %, more preferably 8 to 18 wt %, even more preferably 10 to 14.5 wt %, further preferably 11 to 14 wt %, and most preferably 11.5 to 13.5 wt %, in which case the impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0086] As an example, the (D) phosphorus flame retardant may be an aromatic phosphate compound, preferably one or more selected from bisphenol A diphenyl phosphate, bisphenol A bis(diphenyl phosphate), triphenyl phosphate and resorcinol bis(diphenyl phosphate), more preferably bisphenol A bis(diphenyl phosphate), in which case the impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0087] As an example, the (D) phosphorus-based flame retardant may be a halogen-free flame retardant, which is more environmentally friendly.
[0088] (E) Flame retardant additives
[0089] As an example, in the total 100 weight % of the thermoplastic resin composition, the content of the (E) flame retardant aid can be 0.1 to 5 weight %, preferably 0.1 to 3 weight parts, more preferably 0.3 to 2 weight parts, and even more preferably 0.3 to 1.7 weight parts. In this case, impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0090] As an example, the flame retardant may include a fluorine-based flame retardant. As a specific example, the fluorine-based flame retardant may be one or more selected from polytetrafluoroethylene (PTFE) and tetrafluoroethylene-hexafluoropropylene (TFE-HFP). In this case, the flame retardant efficiency is more outstanding.
[0091] As a more specific example, the fluorine-based flame retardant additive may be one or more selected from PTFE, a combination of PTFE and polymethyl methacrylate (PMMA) resin (PTFE / PMMA), and a combination of PTFE and styrene-acrylonitrile (SAN) resin (PTFE / SAN). Preferably, the PTFE / SAN and PTFE / PMMA are mixed in a weight ratio of 1:0.5 to 1.5 for PTFE and SAN or PMMA, respectively. As an embodiment, they may be mixed in a weight ratio of 1:1, respectively.
[0092] (F) Wollastonite
[0093] As an example, in the total 100 wt % of the thermoplastic resin composition, the content of the (F) wollastonite can be 10 to 26 wt %, preferably 10 to 23 wt %, more preferably 12 to 23 wt %, and even more preferably 10 to 26 wt %, in which case the impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0094] The (F) wollastonite may be represented by the chemical formula CaSiO3 or CaO·SiO2, may be needle-shaped, and may have a specific gravity of 2.8 to 3.2.
[0095] The Mohs hardness of the (F) wollastonite may be about 4.5.
[0096] As an example, the (F) wollastonite may be surface treated with a surface treatment agent such as a silane crosslinking agent. In this case, the mechanical properties and molding processability are further improved.
[0097] In the present invention, the surface treatment method of wollastonite and the amount of the surface treatment agent are not particularly limited, as long as they are the surface treatment method and amount commonly used in the art.
[0098] (G) Talc
[0099] As an example, in the thermoplastic resin composition having a total weight of 100%, the content of the talc (G) may be 3 to 20% by weight, preferably 5 to 17% by weight, more preferably 5 to 15% by weight, and even more preferably 5 to 12% by weight. In this case, the impact resistance, molding processability, heat resistance, and flame retardancy are all excellent.
[0100] As an example, the average particle size of the talc (G) may be less than 9 μm, preferably 1 to 8.9 μm, more preferably 3 to 8.9 μm, even more preferably 3 to 6.9 μm, and even more preferably 3 to 5 μm. In this case, the mechanical properties and molding processability are further improved.
[0101] In the present invention, the average particle size of the inorganic particles can be measured by a method commonly used in the art. For example, the major axis particle sizes of 30 or more particles can be measured using a scanning electron microscope (SEM) and the average value can be calculated.
[0102] As an example, the talc (G) may be surface-treated with a surface treatment agent such as a silane crosslinking agent, polyethylene glycol, an unsaturated organic acid, or a fatty acid metal salt. In this case, the mechanical properties and molding processability are further improved.
[0103] In the present invention, the surface treatment method of talc and the amount of the surface treatment agent are not particularly limited, as long as they are the surface treatment method and amount commonly used in the art.
[0104] (H) Antioxidant, lubricant or a combination of both
[0105] As an example, in a total of 100 wt % of the thermoplastic resin composition, the content of the (H) antioxidant, lubricant or a combination of the two can be 0.05 to 5 wt %, preferably 0.1 to 4 wt %, more preferably 0.1 to 3 wt %, and even more preferably 0.2 to 2 wt %, in which case impact resistance, molding processability, heat resistance and flame retardancy are all excellent.
[0106] As a specific example, the content of the antioxidant can be 0.05 to 2 weight %, preferably 0.05 to 1 weight %, more preferably 0.1 to 1 weight %, and even more preferably 0.1 to 0.5 weight %. The content of the lubricant can be 0.05 to 3 weight %, preferably 0.1 to 2.5 weight %, more preferably 0.1 to 2 weight %, and even more preferably 0.2 to 1 weight %.
[0107] The (H) is preferably a combination of an antioxidant and a lubricant.
[0108] As an example, the antioxidant in (H) may include one or more selected from phenolic antioxidants and phosphorus antioxidants, preferably including both phenolic antioxidants and phosphorus antioxidants. In this case, the physical stability of the composition can be improved, and therefore the target physical properties can be fully achieved.
[0109] The weight ratio of the phenol antioxidant to the phosphorus antioxidant is preferably 1:0.5-2, more preferably 1:0.8-1.5, and even more preferably 1:0.8-1.1. In this case, the target physical properties can be fully achieved without reducing other physical properties.
[0110] As an example, the phenolic antioxidant may be selected from N,N′-hexane-1,6-diyl-bis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)], pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate At least one of tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], CAS No.: 6683-19-8), N,N′-hexamethylene-bis (3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid), triethylene glycol-bis [3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate, 1,3,5-trimethyl-2,4,6-tris (3,5-di-tert-butyl-4-hydroxybenzyl) benzene, 1,3,5-tris (4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate and hindered phenol heat stabilizer can be used. At this time, it is possible to maintain a high balance of physical properties and greatly improve heat resistance.
[0111] As an example, the hindered phenolic heat stabilizer can be selected from octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (CAS No.: 2082-79-3), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), hexanediol-bis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate), triethylene glycol-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxy-benzyl)benzene, n-octadecyl-3-(4'-hydroxy-3' The heat stabilizer is preferably one or more of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 4,4'-methylenebis(2,6-di-tert-butylphenol), 4,4'-butylene-bis(6-tert-butyl-3-methylphenol), distearyl-3,5-di-tert-butyl-4-hydroxybenzyl phosphate, 2-tert-butyl-6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)-4-methylphenyl acrylate, and 3,9-bis{2-〔3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy〕-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro〔5,5〕undecane. The heat stabilizer is preferably pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, or a combination thereof.
[0112] As an example, the phosphorus antioxidant can be selected from triphenyl phosphite, tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(2,6-di-tert-butylphenyl) phosphite, tridecyl phosphite, trioctyl phosphite, tri(octadecyl) phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl One or more of phosphite, monooctyl diphenyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, bis(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, stearyl pentaerythritol diphosphite, tributyl phosphate, triethyl phosphate and trimethyl phosphate.
[0113] As an example, the lubricant in (H) may include one or more selected from fatty amide compounds, lignite wax, silicone oil, olefin wax and pentaerythritol stearate, preferably olefin wax. In this case, the molding processability and mold release properties are excellent, and therefore the appearance of the molded product is more outstanding.
[0114] As an example, the fatty amide compound can be one or more selected from stearamide, behenamide, ethylene bis(stearamide), ethylene bis(12-hydroxystearamide), erucamide, oleamide and ethylene bisoleamide.
[0115] As an example, the montan wax may be montan wax, montan ester wax or a combination thereof.
[0116] As an example, the silicone oil may be one or more selected from dimethyl silicone oil, methyl hydrogen silicone oil, ester-modified silicone oil, hydroxy silicone oil, methanol-modified silicone oil, vinyl silicone oil, and silicone acrylate.
[0117] As an example, the olefin wax may be polyethylene wax, polypropylene wax or a combination thereof. As an example, the polyethylene wax may include oxidized high-density polyethylene wax.
[0118] As an example, the pentaerythritol stearate may be one or more of pentaerythritol monostearate, pentaerythritol dirastearate, and pentaerythritol tetrastearate.
[0119] As an example, the lubricant in (H) may further include an organic fatty acid ester release agent and / or a synthetic wax, specifically, based on 100 parts by weight of the thermoplastic resin mixture of (A) to (C), it may include 0.05 to 2 parts by weight, preferably 0.1 to 1 part by weight.
[0120] As an example, the organic fatty acid ester release agent may be one or more selected from zinc laurate, calcium laurate, zinc stearate, calcium stearate, aluminum stearate, magnesium stearate, zinc myristic acid, calcium montanate, zinc montanate, aluminum montanate, calcium behenate, magnesium behenate and zinc behenate.
[0121] As an example, the synthetic wax may be one or more selected from modified hydrocarbon wax and mineral oil synthetic wax. The modified hydrocarbon wax and mineral oil synthetic wax are not particularly limited, as long as the modified hydrocarbon wax and mineral oil synthetic wax commonly used in the art are used.
[0122] Thermoplastic resin composition
[0123] Preferably, the thermoplastic resin composition may include: 51 to 70 weight % of (A) post-consumer recycled polycarbonate resin; 2 to 12 weight % of (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 2 to 11 weight % of (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 3 to 20 weight % of (D) phosphorus flame retardant; 0.1 to 5 weight % of (E) flame retardant auxiliary; 10 to 26 weight % of (F) wollastonite; 3 to 20 weight % of (G) talc; and 0.05 to 5 weight % of (H) antioxidant, lubricant or a combination of the two. In this case, the composition is environmentally friendly due to the inclusion of recycled resin, and has excellent impact resistance, molding processability, heat resistance and flame retardancy.
[0124] As an example, the (F) wollastonite and (G) talc may be included in a weight ratio of 1:0.1 to 1:0.9 (F:G), preferably in a weight ratio of 1:0.3 to 1:0.9. In this case, even if a high content of recycled resin is included, excellent impact resistance, molding processability, heat resistance and flame retardancy are provided.
[0125] Preferably, the thermoplastic resin composition may include: 51 to 70 weight % of (A) post-consumer recycled polycarbonate resin; 2 to 12 weight % of (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 2 to 11 weight % of (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 3 to 20 weight % of (D) phosphorus flame retardant; 0.1 to 5 weight % of (E) flame retardant auxiliary; 10 to 26 weight % of (F) wollastonite; 3 to 20 weight % of (G) talc; and 0.05 to 5 weight % of (H) antioxidant, lubricant or a combination of the two. As an example, the (F) wollastonite and (G) talc may be included in a weight ratio of 1:0.1 to 1:0.9 (F:G). In this case, impact resistance, molding processability and heat resistance are more excellent.
[0126] As an example, in the thermoplastic resin composition, the sum of the weights of the (B) graft copolymer and the (C) graft copolymer (B+C) can be less than 13% by weight, preferably 8 to 12.9% by weight, and more preferably 9 to 12.8% by weight. In this case, the impact resistance is further improved without reducing other physical properties.
[0127] As an example, in the thermoplastic resin composition, the weight ratio [(B+C) / D] obtained by dividing the sum of the weights of the (B) graft copolymer and the (C) graft copolymer by the weight of the (D) phosphorus flame retardant may be less than 1, specifically 0.70 to 0.99, preferably 0.70 to 0.95, and more preferably 0.70 to 0.90. In this case, the physical properties of impact resistance and flame retardancy are well balanced without reducing other physical properties.
[0128] In the present invention, unless otherwise specified, the content means weight %.
[0129] As an example, according to the ASTM D256 standard, the impact strength of the thermoplastic resin composition measured under the condition that the sample thickness is 3.2 mm can be 5 kgf / cm·cm or more, preferably 5 to 20 kgf / cm·cm, more preferably 5 to 15 kgf / cm·cm, and even more preferably 5 to 12 kgf / cm·cm. Within this range, the impact resistance and the balance of physical properties are more excellent.
[0130] For example, according to ISO 1133, the flow index of the thermoplastic resin composition measured at a temperature of 260° C. and a load of 2.16 kg may be 6.0 g / 10 min or more, preferably 6.0 to 20.0 g / 10 min. Within this range, the molding processability and the balance of physical properties are more excellent.
[0131] As an example, according to the ASTM D648 standard, the heat deformation temperature of the thermoplastic resin composition measured under the conditions of a sample thickness of 6.4 mm and a stress of 1.82 MPa can be 85° C. or higher, preferably 85 to 100° C., and more preferably 85 to 97° C. Within this range, the balance between heat resistance and physical properties is more excellent, and molding processing can be smoothly performed to manufacture molded products with uniform quality, thereby improving the product reliability of the molded products.
[0132] Preferably, according to ASTM D256, the impact strength of the thermoplastic resin composition measured under the condition that the sample thickness is 3.2 mm can be 5 to 20 kgf / cm·cm, according to ISO 1133, the flow index of the thermoplastic resin composition measured under the conditions of a temperature of 260° C. and a load of 2.16 kg can be 6.0 to 20.0 g / 10 min, and according to ASTM D648, the heat deformation temperature of the thermoplastic resin composition measured under the conditions that the sample thickness is 6.4 mm and the stress is 1.82 MPa can be 85 to 100° C. Within this range, the thermoplastic resin composition has both impact resistance and molding processability suitable for components of electrical and electronic products and improves product reliability.
[0133] Preferably, the flame retardancy of the thermoplastic resin composition measured under the conditions of length, width and thickness of 127 mm×12.7 mm×0.8 mm according to UL94 standard (Vertical Burning Test) can be V-0 grade or above, and can provide flame retardancy suitable for parts used in electrical and electronic products without reducing other physical properties.
[0134] When the components (A) to (G) or (H) are included, the thermoplastic resin composition may further selectively include, in addition to the components (A) to (H), 0.01 to 10 parts by weight, 0.05 to 7 parts by weight, 0.1 to 5 parts by weight or 0.5 to 4.5 parts by weight of other additives selected from UV stabilizers, pigments, antistatic agents, bactericides, compatibilizers, metal deactivators, smoke suppressants, matting agents, antifriction agents and anti-wear agents, based on 100 parts by weight of the total of the components (A) to (G), as required. Within this range, the target properties of the thermoplastic resin composition of the present invention are not reduced and the target properties are well achieved.
[0135] As an example, the UV stabilizer can be one or more selected from triazine ultraviolet absorbers, benzophenone ultraviolet absorbers, benzotriazole ultraviolet absorbers, indole ultraviolet absorbers, quinolinone ultraviolet absorbers, benzoate ultraviolet absorbers, cyanoacrylate ultraviolet absorbers and benzoxazole ultraviolet absorbers, preferably a benzotriazole ultraviolet absorber. In this case, the physical property balance is excellent and the light resistance is further improved.
[0136] As an example, the triazine ultraviolet absorber can be 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine. 3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine Tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4 ,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(2-(2-ethylhexanoyloxy)ethoxy)phenol. ,
[0137] As an example, the benzophenone-based ultraviolet absorber can be selected from 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone (2-hydroxy-4-methoxy-5-sulfoxybenzophenone), 2-hydroxy-4-methoxy-5-sulfonic acid trihydrate benzophenone (2-hydroxy-4-methoxy-5-sulfoxytrihydratebenzophenone), 2-hydroxy-4-dodecyloxy-benzophenone, 2-hydroxy-4-octadecyloxy-benzophenone, 2,2'-dihydroxy-4-methoxy At least one of benzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodiumsulfoxybenzophenone, 5,5-methylenebis(2-hydroxy-4-methoxybenzophenone) (bis(5-benzoyl-4-Hydroxy-2-methoxyphenyl)methane), 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone and 4,4'-bis(diethylamino)benzophenone.
[0138] As an example, the benzotriazole ultraviolet absorber can be selected from 2-2'-hydroxy-3', 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 5'-bis(α,α-dimethylbenzyl)phenyl-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5' -di-tert-butyl-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-pentyl)-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-pentylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[ 4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3',5'-bis(1-methyl-1-phenylethyl)-2'-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole (CAS No. 2440-22-4), 2-(3',5'-di-tert-butyl-2'-hydroxyphenyl)benzotriazole, 2-(5'-tert-butyl-2'-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol 2-(3',5'-di-tert-butyl-2'-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3'-tert-butyl-2'-hydroxy-5'-methylphenyl)-5-chlorobenzotriazole, 2-(3'-sec-butyl-5'-tert-butyl-2'-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-4'-octyloxyphenyl)benzotriazole, 2-(3',5'-di-tert-amyl-2'-hydroxyphenyl)benzotriazole, 2-(3',5'-bis(α,α-dimethylbenzyl)-2'-hydroxyphenyl)benzotriazole, 2-(3'-tert-butyl-2'-hydroxy-5'-(2-octyloxy-carbonylethyl)phenyl)-5-chlorobenzotriazole, 2-(3'-tert-butyl-5'-[2-(2-ethylhexyloxy)carbonylethyl]-2'-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3'-tert-butyl-2'-hydroxy-5'-(2-methoxycarbonylethyl)phenyl)-5-chlorobenzotriazole, 2-(3'-tert-butyl-2'-hydroxy-5'-(2-methoxycarbonylethyl)phenyl)benzotriazole, 2-(3'-tert-butyl-2'-hydroxy-5'-(2-octyloxycarbonylethyl)phenyl) At least one of 2-(3'-tert-butyl-5'-[2-(2-ethylhexyloxy)carbonylethyl]-2'-hydroxyphenyl)benzotriazole, 2-(3'-dodecyl-2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(3'-tert-butyl-2'-hydroxy-5'-(2-isooctyloxycarbonylethyl)phenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-benzotriazol-2-ylphenol] and ester exchange products of 2-[3'-tert-butyl-5'-(2-methoxycarbonylethyl)-2'-hydroxyphenyl]-2H-benzotriazole and polyethylene glycol.
[0139] As an example, the indole-based ultraviolet absorber may be 2-[(1-methyl-2-phenyl-1H-indol-3-yl)methylene]malononitrile.
[0140] As an example, the quinolinone-based ultraviolet absorber may be 4-hydroxy-3-[(phenylimino)methyl]-2(1H)-quinolinone.
[0141] As an example, the benzoate ultraviolet absorber can be one or more selected from 2,4-di-tert-butylphenyl-3',5'-di-tert-butyl-4'-hydroxybenzoate, 2,6-di-tert-butylphenyl-3',5'-di-tert-butyl-4'-hydroxybenzoate, n-hexadecyl-3,5-di-tert-butyl-4-hydroxybenzoate and n-octadecyl-3,5-di-tert-butyl-4-hydroxybenzoate.
[0142] As an example, the cyanoacrylate-based ultraviolet absorber may be 2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, or a combination thereof.
[0143] The pigment may be an inorganic pigment or an organic pigment.
[0144] As an example, the organic pigment can be one or more selected from pyrenone pigments, anthraquinone pigments, perylene pigments, phthalocyanine pigments, azo pigments, indigo pigments, dioxazine pigments, quinacridone pigments, methane pigments, quinoline pigments, isoindolinone pigments and phthalocyanine pigments.
[0145] As an example, the inorganic pigment may be one or more selected from ultramarine pigments, titanium dioxide, zinc sulfide, zinc oxide, iron oxide, magnesium oxide, aluminum hydroxide, carbon black, and white carbon.
[0146] As an example, the antistatic agent may include one or more anionic surfactants, nonionic surfactants, etc., but is not limited thereto.
[0147] The bactericide, processing aid, metal passivator, smoke suppressant, matting agent, anti-friction agent, anti-wear agent, etc. are not particularly limited as long as they are commonly used in the art.
[0148] Method for preparing thermoplastic resin composition
[0149] The preparation method of the thermoplastic resin composition comprises the steps of kneading and extruding a mixture containing (A) post-consumer recycled polycarbonate resin, (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer, (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer, (D) phosphorus flame retardant, (E) flame retardant auxiliary, (F) wollastonite, (G) talc and (H) antioxidant, lubricant or a combination of the two, wherein the content of (A) post-consumer recycled polycarbonate resin is 46 to 70% by weight, and the weight ratio of (F) wollastonite to (G) talc is 1:0.1 to 1:0.9 (F:G). At this time, the composition is environmentally friendly due to the inclusion of recycled resin, and has excellent impact resistance, molding processability, heat resistance and flame retardancy.
[0150] As an example, the kneading and extruding steps can be performed at a temperature and a screw rotation speed of the extruder of 200-300°C and 200-350 rpm, respectively, preferably at 220-280°C and 240-300 rpm, at which time, impact resistance, molding processability, heat resistance and flame retardancy are excellent.
[0151] As an example, the kneading and extruding steps can be performed using one or more selected from a single-screw extruder, a twin-screw extruder, and a Banbury mixer, and the composition can be mixed uniformly and then extruded to obtain a thermoplastic resin composition in the form of pellets, in which case the mechanical properties are prevented from being reduced, the heat resistance is reduced, and the appearance quality is excellent.
[0152] Molded products
[0153] The molded article of the present invention includes the thermoplastic resin composition. In this case, the composition contains a recycled resin and is environmentally friendly. The composition also has excellent impact resistance, moldability, heat resistance, and flame retardancy.
[0154] The molded product can be manufactured by a method commonly used in the art. As an example, the molded product can be manufactured by using a melt kneaded product or pellets of the thermoplastic resin composition of the present invention as a raw material and by using a molding method such as injection molding, injection compression molding, extrusion molding, blow molding, compression molding, gas pressure molding, hot bending molding, compression molding, calendaring molding or rotational molding. At this time, the size, thickness, shape, etc. of the molded product can be appropriately adjusted according to the purpose of use.
[0155] Preferably, the molded product can be manufactured by the step of injection molding the molten kneaded product or pellets of the thermoplastic resin composition using an injection molding machine. The molded product thus manufactured has excellent impact resistance, molding processability, heat resistance and flame retardancy, and is therefore suitable for use in electrical and electronic components, preferably covers or bezels of electrical and electronic components.
[0156] Figure 1 is a schematic diagram showing a frame made of the thermoplastic resin composition of the present invention included in a notebook computer, Figure 1 In, A-cover refers to the rear surface cover of the display, B-cover refers to the frame, C-cover refers to the keyboard board (palm rest), and D-cover refers to the bottom cover supporting the laptop computer. The frame, as a frame component that wraps the edge of the display, has the function of supporting and protecting the display. With the recent trend of lightweight and diversified design of electrical and electronic products, especially notebook computer products, the demand for using lighter materials to make components such as external covers (housings) or frames thinner is increasing, and the molded product containing the thermoplastic resin composition of the present invention has flame retardancy suitable for electrical and electronic components, and can ensure impact resistance and molding processability above the specified level, therefore, it is easy to carry out more refined molding processing, and sufficient strength can be achieved at a thinner thickness, and in addition, it has heat resistance suitable for injection molding, thereby improving product reliability, and therefore, it can meet the market demand as described above.
[0157] When describing the thermoplastic resin composition, the method for producing the same, and the molded article of the present invention, other conditions or equipment not explicitly described are not particularly limited and may be appropriately selected within the range of common practice in the art.
[0158] Below, preferred embodiments are proposed to help understand the present invention, but the following embodiments are only used to illustrate the present invention. Those skilled in the art can make various changes and modifications within the scope of the scope of the present invention and technical ideas, and such deformation and modification belong to the scope of the attached claims.
[0159] [Example]
[0160] The materials used in Examples and Comparative Examples are as follows.
[0161] (A) Post-consumer recycled polycarbonate resin: PC resin with a flow index of 10 g / 10 min at 260°C and 2.16 kg according to ISO 1133
[0162] (A') Unprocessed polycarbonate resin: PC resin having a flow index of 10 g / 10 min at 260°C and 2.16 kg according to ISO 1133
[0163] (B) Vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer: ABS resin (Sinopec Corporation, product name: ABS8391) having a Mw (weight average molecular weight) of 50,000 to 100,000 g / mol, 60 to 70% by weight of butadiene rubber, 10 to 20% by weight of styrene, and 10 to 20% by weight of acrylonitrile.
[0164] (C) (Meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer: Mw of 100,000 to 150,000 g / mol, butadiene rubber of 62 to 75% by weight, methyl methacrylate-butadiene-styrene (MBS) resin having a methyl methacrylate unit content of 15 to 32% by weight (LG Chemical Company, product name: MB538)
[0165] (D) Phosphorus flame retardant: bisphenol-A-bis(diphenyl phosphate) flame retardant
[0166] (E) Flame retardant additive: PTFE (polytetrafluoroethylene)
[0167] (F) Wollastonite: needle-shaped, average particle size 7 to 9 μm (KOCH, SFC5-4101)
[0168] (G) Talc:
[0169] (G1) Talc (Koch, KC-3000C), flake-shaped, average particle size 3-5 μm
[0170] (G2) Talc (Koch Corporation, KC-6300C), average particle size 9 μm
[0171] (G3) Talc (Koch Company, KC-3CA), flake-shaped, average particle size greater than 10 μm
[0172] (H) Antioxidants, lubricants or a combination of the two:
[0173] (H1) Phenol antioxidant: N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide))
[0174] (H2) Phosphorus antioxidant: Tris(2,4-di-t-butylphenyl)Phosphite
[0175] (H3) Lubricant: Bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol-di-phosphite
[0176] Examples 1 to 3 and Comparative Examples 1 to 5
[0177] The (A) post-consumer recycled polycarbonate resin to the (H3) lubricant were mixed using a super mixer according to the contents shown in Table 1, and extruded using a twin-screw extruder (screw diameter: 26 mm, L / D=40) at an extrusion temperature of 260° C. and a screw rotation speed of 270 rpm to produce a pellet form.
[0178] After drying the thermoplastic resin composition in pellet form at 100°C for more than 2 hours, injection molding was performed in an injection molding machine at an injection temperature of 260°C, a mold temperature of 60°C, and an injection speed of 30 mm / sec to produce a sample, and the sample was left at room temperature (20-26°C) for more than 48 hours, and then the physical properties were measured.
[0179] [Experimental example]
[0180] The physical properties of the samples prepared in the examples and comparative examples were measured by the following methods, and the results are shown in Table 1.
[0181] * Impact strength (kgf / cm·cm): measured in accordance with ASTM D256 at 23°C with a specimen thickness of 3.2 mm and a notch width of 2.54 mm.
[0182] * Melt flow index (g / 10 min): According to ISO 1133, the weight (g) of the resin melted out in 10 minutes is measured under the conditions of a temperature of 260° C. and a load of 2.16 kg.
[0183] *Heat deformation temperature (°C): measured in accordance with ASTM D648, using a 6.4 mm thick specimen under a stress of 1.82 MPa.
[0184] * Flame retardancy: measured according to UL94 standard (Vertical Burning Test) using injection molded specimens with a width of 127 mm x 12.7 mm and a thickness of 0.8 mm.
[0185] Table 1:
[0186]
[0187]
[0188] Referring to Table 1 above, it can be confirmed that even if recycled resin is used, Examples 1 to 3 manufactured according to the present invention show an impact strength of 5.33 kgf / cm·cm or more, a flow index of 7.02 g / 10 min or more, a heat deformation temperature of 85.2°C or more, and a flame retardancy of V-0 level, and excellent impact resistance, molding processability, heat resistance and flame retardancy. In addition, it can be confirmed that Example 3, in which the content of talc in the mixture of wollastonite and talc is increased, has improved impact resistance compared to Comparative Example 4 in which recycled resin is not used. Not only that, it also shows the same level of heat resistance, and therefore, it can replace the unprocessed resin composition.
[0189] In contrast, in Comparative Examples 1 to 3 using only one of wollastonite and talc, the flame retardancy, molding processability, and heat resistance were not improved compared with Examples 1 to 3, and one of the properties was significantly reduced.
[0190] For reference, Comparative Example 5 in which the talc (G1) used in Example 3 was replaced with talc (G2) exhibited an impact strength of 5.56 kgf / cm·cm, a melt index of 5.89 g / 10 min, a heat deformation temperature of 86.1°C, and a flame retardancy of V-1. Therefore, it can be confirmed that the type of talc affects molding processability and flame retardancy.
[0191] In summary, the thermoplastic resin composition of the present invention is obtained by mixing an impact-reinforcing resin, a flame retardant, a filler, etc. into a predetermined recycled resin and adjusting the combination ratio, thereby improving the degradation of physical properties caused by the recycled resin while having excellent flame retardancy, impact resistance, molding processability, etc. Therefore, it is possible to provide a thermoplastic resin composition suitable for molded products such as covers and frames of electrical and electronic components.
Claims
1. A thermoplastic resin composition, characterized in that include: (A) post-consumer recycled polycarbonate resin; (B) a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (C) a (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (D) a phosphorus flame retardant; (E) a flame retardant auxiliary; (F) wollastonite; (G) talc; and (H) an antioxidant, a lubricant, or a combination thereof, Wherein, the content of the post-consumer recycled polycarbonate resin (A) is 46 to 70% by weight, According to ASTM D256, the impact strength of the thermoplastic resin composition measured under the condition that the sample thickness is 3.2 mm is 5 kgf / cm.cm or more. According to ISO 1133, the flow index of the thermoplastic resin composition measured under the conditions that the temperature is 260° C. and the load is 2.16 kg is 6 g / 10 min or more. According to ASTM D648, the heat deformation temperature of the thermoplastic resin composition measured under the conditions that the sample thickness is 6.4 mm and the stress is 1.82 MPa is 85° C. or more.
2. A thermoplastic resin composition, characterized in that include: (A) post-consumer recycled polycarbonate resin; (B) a vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (C) a (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; (D) a phosphorus flame retardant; (E) a flame retardant auxiliary; (F) wollastonite; (G) talc; and (H) an antioxidant, a lubricant, or a combination thereof, Wherein, the content of the post-consumer recycled polycarbonate resin (A) is 46 to 70% by weight, The weight ratio of the (F) wollastonite to the (G) talc is 1: 0.1~1:0.9, The average particle size of the talc (G) is less than 9 μm.
3. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The thermoplastic resin composition comprises: 51 to 70 weight percent of (A) post-consumer recycled polycarbonate resin; 2 to 12 weight percent of (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 2 to 11 weight percent of (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer; 3 to 20 weight percent of (D) phosphorus flame retardant; 0.1 to 5 wt% of (E) a flame retardant additive; 10 to 26 wt% of (F) wollastonite; 3 to 20 wt% of (G) talc; and 0.05 to 5 wt% of (H) an antioxidant, a lubricant, or a combination thereof.
4. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The (A) post-consumer recycled polycarbonate resin has a flow index of 3 to 17 g / 10 min measured at 300° C. and 1.2 kg according to ISO 1133 standard.
5. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer comprises 40-80 wt % of conjugated diene rubber, 5-35 wt % of aromatic vinyl compound and 5-35 wt % of vinyl cyanide compound.
6. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The (C) (meth)acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer comprises 40-80 wt % of conjugated diene rubber, 10-40 wt % of aromatic vinyl compound and 2-25 wt % of (meth)acrylate alkyl ester compound.
7. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The (D) phosphorus flame retardant is at least one selected from bisphenol A bis(diphenyl phosphate), triphenyl phosphate and resorcinol bis(diphenyl phosphate).
8. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The (E) flame retardant auxiliary agent includes a fluorine-based flame retardant auxiliary agent.
9. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The average particle size of the talc (G) is 3 to 5 μm.
10. The thermoplastic resin composition according to claim 1 or 2, characterized in that: The (H) antioxidant, lubricant or a combination of the two comprises at least one selected from phenolic antioxidants and phosphorus antioxidants as the antioxidant, and comprises at least one selected from fatty amide compounds, lignite wax, silicone oil, olefin wax and pentaerythritol stearate as the lubricant.
11. A method for preparing a thermoplastic resin composition, characterized in that: The invention comprises the steps of kneading and extruding a mixture containing (A) post-consumer recycled polycarbonate resin, (B) vinyl cyanide compound-conjugated diene compound-aromatic vinyl compound graft copolymer, (C) (meth) acrylate alkyl ester compound-conjugated diene compound-aromatic vinyl compound graft copolymer, (D) phosphorus flame retardant, (E) flame retardant auxiliary, (F) wollastonite, (G) talc and (H) antioxidant, lubricant or a combination of both, The content of the post-consumer recycled polycarbonate resin (A) is 46 to 70% by weight, The weight ratio of the (F) wollastonite to the (G) talc is 1: 0.1~1:0.9, The average particle size of the talc (G) is less than 9 μm.
12. A molded product, characterized in that: A thermoplastic resin composition comprising the thermoplastic resin composition according to claim 1 or 2.
13. The molded article according to claim 12, characterized in that The molded product is a cover or frame of an electric or electronic component.
Citation Information
Patent Citations
Scratch-resistant flameproof thermoplastic resin composition
KR100767428B1